2015
DOI: 10.1016/j.eurpsy.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between schematic beliefs, bullying, and unusual experiences in 8–14 year olds

Abstract: Children's NSBs may mediate the adverse psychological impact of victimisation, and are appropriate treatment targets for young people with UEDs. Early educational intervention to reduce negative appraisals of the self and others may increase resilience to future adverse experiences and reduce later mental health risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
2
8
0
1
Order By: Relevance
“…This can be exacerbated when victimization, threat, and danger also occur within the family home (Radford, Corral, Bradley, & Fisher, 2013 ) and local neighborhood (Jack & Egan, 2016 ). Relatedly, Anilmis et al ( 2015 ) reported that, in a child sample, negative schematic beliefs about the self and others mediated the relationship between bullying and psychotic-like experiences; similar findings have been reported by Campbell and Morrison ( 2007 ) and Chaudhry ( 2012 ). Further, evidence indicates that victims of childhood bullying experience depression, anxiety, and lower self-esteem (Hawker & Boulton, 2000 ), negative self-related cognitions (Cook, Williams, Guerra, Kim, & Sadek, 2010 ) and can develop a hostile attribution bias (the perception that others’ neutral actions are conducted with hostility: Dodge, 2006 ; Pornari & Wood, 2010 ).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…This can be exacerbated when victimization, threat, and danger also occur within the family home (Radford, Corral, Bradley, & Fisher, 2013 ) and local neighborhood (Jack & Egan, 2016 ). Relatedly, Anilmis et al ( 2015 ) reported that, in a child sample, negative schematic beliefs about the self and others mediated the relationship between bullying and psychotic-like experiences; similar findings have been reported by Campbell and Morrison ( 2007 ) and Chaudhry ( 2012 ). Further, evidence indicates that victims of childhood bullying experience depression, anxiety, and lower self-esteem (Hawker & Boulton, 2000 ), negative self-related cognitions (Cook, Williams, Guerra, Kim, & Sadek, 2010 ) and can develop a hostile attribution bias (the perception that others’ neutral actions are conducted with hostility: Dodge, 2006 ; Pornari & Wood, 2010 ).…”
Section: Introductionsupporting
confidence: 65%
“…Cognitive bias is implicated in the development of paranoid thinking (Freeman & Garety, 2014 ). Smith et al ( 2006 ) have argued that experiences of victimization contribute toward the development of schematic beliefs concerning danger, and Corcoran et al ( 2006 ) have identified that such internalized beliefs manifest as an availability heuristic when paranoid thinkers appraise situations for threat; this has also been demonstrated in a sample of bullied adolescents (Anilmis et al, 2015 ). The results of the present study appear to uphold these findings.…”
Section: Discussionmentioning
confidence: 99%
“…These will be assessed at 0, 16 and 24 weeks. Areas assessed include child self-reported mood and behaviour problems (anxiety, depression, elevated mood, anger, hyperactivity, conduct disorder and peer problems) [ 41 , 42 , 55 – 59 ]; child-reported trauma sequelae, emotional regulation, substance misuse and eating disorders [ 45 , 60 63 ]; activity levels, social support and sleep pattern [ 64 – 66 ], appraisals of the self and others, UEDs and the presenting problem [ 27 , 28 , 67 – 72 ]; and reasoning style [ 73 ]. Parent/carer measures will be completed at 0 and 16 weeks, and will include the 5-min speech sample to assess family relationships [ 74 ], and measures of parental affect, wellbeing, caregiving experience, and coping [ 75 79 ], as well as parental assessments of child mood and behaviour difficulties and UEDs [ 10 , 14 , 41 , 42 , 55 – 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive models of psychosis have highlighted the role of negative schematic beliefs in the association between psychotic symptoms and adverse events (Fisher 2012). Anilmis et al (2015) analysed the role of negative schematic beliefs about the self and others (as mediators between bullying victimisation and distressing unusual experiences) in 8- to 14-year-olds referred to child and adolescent mental health services. Their findings strongly support the view that negative beliefs following a stressful event may lead to PLEs.…”
Section: Theoretical Explanations For the Association Between Bullyinmentioning
confidence: 99%